2017
DOI: 10.1093/biolre/iox087
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1 increases Kiss-1 mRNA expression in kisspeptin-expressing neuronal cells†

Abstract: Feeding-related metabolic factors exert regulatory influences on the hypothalamic-pituitary-gonadal axis. Glucagon-like peptide-1 (GLP-1) is an anorexigenic hormone synthesized from the ileum in response to food intake. The purpose of this study was to examine the direct effect of GLP-1 on hypothalamic kisspeptin and gonadotropin-releasing hormone (GnRH) expression using the rat clonal hypothalamic cell line rHypoE-8. GLP-1 significantly increased Kiss-1 mRNA expression in rHypoE-8 cells up to 1.94 ± 0.22-fold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Earlier studies have shown that GLP-1 can control the HPG axis centrally via interaction with the GnRH system (Beak et al 1998;Farkas et al 2016). Furthermore, its key regulator, the hypothalamic kisspeptin neuron circuit is also influenced by GLP-1 (Oride et al 2017;Heppner et al 2017). In the present study, we have provided compelling evidence for the modulatory role of the brain-derived GLP-1 upon GnRH neurons.…”
Section: Discussionsupporting
confidence: 65%
“…Earlier studies have shown that GLP-1 can control the HPG axis centrally via interaction with the GnRH system (Beak et al 1998;Farkas et al 2016). Furthermore, its key regulator, the hypothalamic kisspeptin neuron circuit is also influenced by GLP-1 (Oride et al 2017;Heppner et al 2017). In the present study, we have provided compelling evidence for the modulatory role of the brain-derived GLP-1 upon GnRH neurons.…”
Section: Discussionsupporting
confidence: 65%
“…33 The gut hormones, GLP-1, PYY and glucagon have key roles in glucose homeostasis. Additionally, in rodent studies, GLP-1 has been shown to alter hypothalamic kisspeptin expression and neuronal activity, 42,43 and in mice glucagon stimulates hepatic kisspeptin production to alter GSIS. 13 In our study, there was no difference in circulating GLP-1, PYY or glucagon levels following intravenous glucose during kisspeptin administration compared to vehicle ( Figure S1C-E).…”
Section: Discussionmentioning
confidence: 99%
“…The GLP-1R-immunoreactive areas were ranked into four categories based on the density of immunoreactive fibers from "+", meaning low level to "++++" meaning "very high" level, and based on the density of immunoreactive perikarya from *meaning low to ***meaning high level The presence of GLP-1R on axon terminals suggests that GLP-1 signaling may regulate the activity of presynaptic terminals and may modulate both GABA and glutamate release. Since the elevation of intracellular cAMP level is one of the main mediators of GLP-1R signaling (Rowlands et al 2018;Kawatani et al 2018;Oride et al 2017), and cAMP is known to increase the release probability in presynaptic terminals (Chen and Regehr 1997), it is likely that GLP-1 and/or GLP-1 agonists increase the activity of the GLP-1R-containing presynaptic terminals. This hypothesis is supported by the findings of Rebosio et al (2018) demonstrating that the GLP-1 agonist exendin-4 increases the GABA and aspartate release from hippocampal synaptosomal preparations, and also by our observation demonstrating facilitation of the synaptic input of POMC neurons by GLP-1 signaling (Péterfi 2020).…”
Section: Table 5 Distribution Of the Glp-1r-ir Structures In The Ponsmentioning
confidence: 99%